The social life of HIV care: On the making of ‘care beyond the virus’ - Rhodes, Tim; Egede, Siri; Grenfell, Pippa; Paparini, Sara; Duff, Cameron (BioSocieties, 2019)
Treating care as an effect of material implementations, we use qualitative interviews with people living with HIV in London, most of whom are migrants, to explore care practices linked to clinical treatment delivered as part of the ‘cascade of HIV care’. We consider how HIV care is done, and what HIV care does, drawing on assemblage theory. We ask how is care affected by the situations in which it is enacted? and what contingent forms of care does the HIV care cascade potentiate? A prime actor in the care assemblages revealed in our study is immigration, from which multiple uncertainties flow, including access to vital resources such as housing and income. Yet we also found that clinical HIV care is worked-with in practice to afford multiple forms of care. Here, viral care is translated into matters of vital concern to produce care which extends ‘beyond the virus’. Practices of care beyond the virus afford social protection, including through making-up social relations and networks, and novel modes of sociality. Friendship connections, community organisations and HIV clinics are among the key actors involved. Being attuned to how HIV care is made to matter helps generate new ways of knowing and doing care.